Implementasi Kurikulum Merdeka Belajar untuk Meningkatkan Mutu Pembelajaran Pendidikan Agama Katolik di SMK Negeri 1 Talibura - Veronika Delvriana Dua Nurak; Hermania Bhoki; Yosep Belen Keban (JURNAL ILMIAH PENDIDIKAN KEBUDAYAAN DAN AGAMA, 2026)
The quality of Catholic Religious Education learning is an important aspect in shaping students’ faith, character, knowledge, and religious life skills. However, the learning process at SMK Negeri 1 Talibura still faces various challenges, particularly in the areas of spiritual attitudes, social attitudes, Catholic religious knowledge, and religious life skills. This study aims to describe the implementation of the Independent Learning Curriculum (Merdeka Belajar Curriculum) and its contribution to improving the quality of Catholic Religious Education learning at SMK Negeri 1 Talibura. The research employed a qualitative approach with a descriptive research design. Data were collected through observations, interviews, and documentation involving the principal, Catholic Religious Education teachers, students, and parents. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results show that the implementation of the Independent Learning Curriculum has been carried out effectively through learning planning, learning implementation, learning assessment, and the Pancasila Student Profile Strengthening Project (P5). This implementation has had a positive impact on the learning process, outputs, and outcomes. Students demonstrated improvements in spiritual attitudes, social attitudes, Catholic religious knowledge, and religious life skills, as well as positive behavioral changes in their daily lives. The findings imply that the Independent Learning Curriculum can serve as an effective strategy for improving the quality of Catholic Religious Education learning in a holistic manner.